Problem-Based Learning on the Learning Perseverance of Indonesian Senior High School Students in Solving Mathematical Problems - Prastiti,Tri Dyah (2020)
Abstract Students should be encouraged to achieve high order thinking skills, in which one of the ways to build the thinking skills is through solving mathematical problems. This study aimed to observe the effectiveness of a problem-based learning method and its effect on students’ perseverance in solving mathematical problems. The subjects of this research were science students at a Senior High School (SMAN) 2 Surabaya, Indonesia, selected with clustered random sampling. The research was conducted with an experimental design, and the problem-based learning method was applied in a Science 1 Class (experiment class), while a Science 4 Class was taught by following the conventional learning method designed by the teacher (control class), where the learning process was centered on the teacher and focused on the discipline. The instruments used in this research were the learning set for both learning methods, initial and final problem sets. The research results showed that the application of problem-based learning methods resulted in better learning outcomes. Moreover, the analysis of covariance showed that the application of a problem-based learning method is effective to develop students’ perseverance in solving mathematical problems.